2005
DOI: 10.1007/s00380-005-0824-x
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular myocardial performance index and exercise capacity in athletes

Abstract: Right ventricular function is important for exercise capacity in athletes. The aim of this study was to investigate the effects of habitual exercise training on right ventricular global function. Fifty-two male athletes (25 runners, 27 wrestlers) and 43 age-matched sedentary male subjects were studied. All subjects in the study underwent an echocardiography examination and cardiopulmonary exercise test. Maximal oxygen consumption, right ventricular cavity diameters, and diastolic parameters were higher in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
3
19
2
Order By: Relevance
“…Observational studies of young male endurance athletes have shown a balanced physiologic hypertrophy of the RV and LV in response to high levels of training (2)(3)(4)(5)(6). The two studies that used MRI included 44 athletes and 31 control subjects (mean age, 25 yr) and found a 22 to 37% increase in RV mass and a 3 to 25% increase in RVEDV in athletes compared with control subjects (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies of young male endurance athletes have shown a balanced physiologic hypertrophy of the RV and LV in response to high levels of training (2)(3)(4)(5)(6). The two studies that used MRI included 44 athletes and 31 control subjects (mean age, 25 yr) and found a 22 to 37% increase in RV mass and a 3 to 25% increase in RVEDV in athletes compared with control subjects (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…The small number of studies performed have shown significant effects of intense exercise on RV mass and volumes (3)(4)(5)(6). However, because RV structure and function are difficult to measure with standard transthoracic echocardiography, little is known about the relationship between physical activity and RV structure and function in large cohorts of adults who are not elite athletes.…”
mentioning
confidence: 99%
“…The athlete's right ventricle. A number of echocardiographic studies have assessed right ventricular geometry and function in both male and female athletes (7)(8)(9)(10). The definition of the RV's complex structure is far superior using CMR.…”
Section: Figure 1 Important Domains Of Study In Athlete's Heartmentioning
confidence: 99%
“…D'Andrea et al (64) reported supra-normal RV free wall myocardial systolic velocities and Kasikcioglu et al (10) reported enhanced RV myocardial performance index values in athletes when compared with control patients. It may be concluded, therefore, that although athletes may have impaired RV function immediately after intense endurance exercise and in the context of ventricular arrhythmias, healthy athletes, at rest, should have RV functional measures that are at least as good as the nonathletic population.…”
Section: A Young Athlete With Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…We therefore did not investigate the effect of strength training or high intensity training, both of which have been advocated as alternatives for dynamic aerobic training in acquired heart disease. 24,25 We measured the echocardiographic parameters at rest. Ideally, we would have presented echocardiographic parameters before and after the intervention measured during exercise.…”
Section: Limitationsmentioning
confidence: 99%